Auto Detection Pot : Smart Technological Pot for Moisture and Temperature Detection - Muhammad Naufal Musaddad; Muhammad Barir Faqih Hermawan; Fahmi Asyrofi Nur Fauzi; BaihaqiNajjar Ammar; Ahnaf Sidqy Fauzi (Jurnal Integrasi Sains dan Quran, 2022)
Pots are one of the most widely used growing media. However, soil moisture and temperature are difficult to see when using a pot as a growing medium. In fact, every plant requires a certain moisture and temperature to achieve maximum productivity and quality. On the other hand, changes in the erratic environmental climate can change the moisture and temperature of a soil. So, it takes pot innovations that can overcome these problems. The purpose of this research is to make an innovation pot, Auto Detection Pot that can detect and give information about the moisture and temperature of the soil. The pot uses Arduino Uno as a microcontroller and soil moisture sensor and temperature sensor as a sensor. This type of research is a qualitative descriptive study where the focus of the description is on making pot innovation, Auto Detection Pot that can detect and give information about moisture and temperature of soil. The method of collection is through observation. The tests were light up tests in three conditions of moisture and temperature of soil, there are not enough, enough, and over. The data obtained in this study were analyzed using descriptive methods. The results showed that the indicator lamps could light up according to the required information regarding moisture and temperature. So, this research has produced Auto Detection Pot as a pot innovation that can detect and give information about moisture and temperature of soil.